Nitridated Fibrous Silica/Tetrabutylammonium Iodide (N‐DFNS/TBAI): Robust and Efficient Catalytic System for Chemical Fixation of Carbon Dioxide to Cyclic Carbonates. Issue 12 (5th May 2021) - Saptal, Vitthal B.; Singh, Rustam; Juneja, Gaurav; Singh, Saideep; Chauhan, Satish M.; Polshettiwar, Vivek; Bhanage, Bhalchandra M.
Abstract: The development of an active and competent catalyst for the conversion of carbon dioxide (CO2 ) to value added‐chemicals at low pressure and temperature have great importance in the field of industrial chemical production as well as in tackling global warming. In this report, nitridated dendritic fibrous nano‐silica (N‐DFNS) as highly porous and stable nano‐material have been synthesized by using ammonolysis reaction at various temperature ranging from 500–800 °C and used as heterogeneous catalysts in combination with TBAI for the synthesis of cyclic carbonates from CO2 and epoxide. The presence of high surface area balanced acid‐base bi‐functionalities generated on silica due to ammonolysis offered high activity towards the synthesis of cyclic carbonates at the atmospheric pressure with excellent recyclability. Abstract : Fixation of Carbon Dioxide : Ammonolysis of dendritic fibrous nano‐silica (DFNS) give amine functionalized mesoporous silica (N‐DFNS) with open pore structures used as heterogeneous catalysts for the synthesis of cyclic carbonates from epoxide and carbon dioxide efficiently.